Feasibility Study of Business Development at Kibo Frizzy Snack - Maharani, Nur; Zulkarnain, Lutfi (ITQAN: Journal of Islamic Economics, Management, and Finance, 2024)
This study aims to analyze the feasibility of developing a business that will be carried out by Kibo Frizzy Snack. The method used in this research is descriptive qualitative. The results of the study show that in the legal aspect, the object is in the form of an individual company and has had a complete and legal permit. On the market and marketing aspects, there are promising opportunities in the future and the market has been wide open. In the technical and operational aspects, it has a well-systematic standard operating procedure and the outlet design layout is in accordance with the company's operational technicalities. In the aspect of organization and management, it has a simple organizational structure and a fairly good management function. In the economic and social aspects, it absorbs some of the workforce of the surrounding community, and helps the sub-culinary government's economic contribution. On the financial aspect, ROI 83%; BEP Q 263; BEP P Rp11,451.